Design, Development, and Evaluation of the Blood Collection Management Workstation - Huang H; Yin H; Xu W; Wang Q; Xiao M; Zhao Q (Dove Medical Press, 2022)
Huanhuan Huang,1 Huimei Yin,2 Wenxin Xu,1 Qi Wang,3 Mingzhao Xiao,4 Qinghua Zhao1 1Department of Nursing, the First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 2Department of Neurology, the First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 3Department of Medical Informatics, the First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 4Department of Urology, Urologist, the First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of ChinaCorrespondence: Qinghua Zhao, Department of Nursing, the First Affiliated Hospital of Chongqing Medical University, 1st Youyi Road, Chongqing, 400016, People's Republic of China, Tel +86 023 89012206, Email qh20063@163.comPurpose: To design and develop a blood collection management workstation with high usability to reduce the risk of preanalytical errors and improve patient safety.Methods: A five-phase mobile application development lifecycle model (MADLC) and experience-based co-design (EBCD) were used for design and development. Subsequently, the blood collection management workstation was evaluated using the Chinese System Usability Scale (SUS) in a general ward setting from January to June 2021.Results: It was used on 2593 in-patients who underwent phlebotomy with 12,378 tubes being labeled. The rate of errors and meantime for blood sampling were decreased compared with the same period in the previous year. A total of 14 nurses agreed to participate in the evaluation, and the overall raw SUS score was 69.26 ± 10.39, which indicated above average results.Conclusion: The blood collection management workstation has shown the potential to decrease errors and improve working efficiency in a clinical setting. The study also identified some weaknesses, which will be amended in the future.Keywords: patient safety, identification, pre-analytical phase, phlebotomy, technology